Participation of TKM Caring for The Elderly in Carrying Out Social Services in Kertaharja Village Sumedang Regency - Rosilawati Rosilawati (International Seminar on Social Work Update, 2023)
Participation is a central concept and basic principle of community development. This is based on the linkage of participation with many things, especially with the idea of human rights, thus making participation a concept that has the aim of activating ideas, the right to participate in democracy, strengthening liberative democracy and as a process of community development. On this basis, TKM that has been formed has the right to actively contribute to social service activities for the elderly. The participation of TKM Cares for the Elderly "Barokah" in this study was measured to what extent the participation of TKM Cares the Elderly "Barokah" from various aspects. This study aims to obtain a general description of the participation of TKM Cares for the Elderly "Barokah" in social services for the elderly in Kertaharja Village, Tanjungkerta District, Sumedang Regency which includes aspects of planning, implementation, and evaluation. This study uses a qualitative approach with a descriptive method. The informants in this study amounted to 3 people. The data collection techniques used were in-depth interviews, observation, and documentation studies. The results of the study indicate that in general the participation of TKM Cares for the Elderly "Barokah" is quite lacking, especially in the aspect of involvement in the implementation of social service activities for the elderly. But the participation of TKM Cares for the Elderly "Barokah" can be increased again.